Ripartire da Dahrendorf: attualità di un inattuale - Segatori, Roberto (SocietàMutamentoPolitica, 2019)
Ralf Dahrendorf has often been considered a “shallow” and untopical author. In the wake of masters such as Kant, Weber and Popper, he went against the tide, posing as an alternative to the German tradition represented by Hegel, Marx and the Frankfurt Institute. With an open methodological approach and a political key oriented towards social liberalism, also inspired by the works of Thomas Marshall and Amartya Sen, he re-elaborated the concepts of class, conflict, life chances, and produced analyzes that led him to denounce the divorce between capitalism and citizenship rights. The article aims to retrace its intellectual itinerary in order to reconsider its possible relevance in a season marked by great inequality, the crisis of social cohesion and the rise of new collective movements in a populist form. In short, both its forecasts on the need for forms of bottom-up democracy and on the risks of the re-emergence of authoritarian temptations in some political regimes are proving to be founded.